Recruitment to the British appellate judiciary, 1876-1972: causal models - Tate, Chester Neal (International political science review, 1992)
This study seeks to advance understanding about the recruitment of judges to the appellate courts in Great Britain, the Court of Appeal and the House of Lords, from the ranks of those serving in the higher British judiciary between 1876 and 1972. Beginning with a literature search to support theory construction to the topic, it postulates a set of interrelated hypotheses explaining this recruitment and states these hypotheses formally and in a causal model. The model is then empirically estimated against data on the background and attributes of the 317 individuals serving in the higher British judiciary from 1876 to 1972. The model confirms well-known propositions about how one advances within the British judiciary, but also documents surprisingly large effects on recruitment for the judges' family social status.